The Influence of the Use of Video-Based Audio Visual Media on Learning Outcomes of Class V Students Theme 2 Clean Air for Health Subtema 1 How the Body Manages Air Clean at State Primary School 097805 Red Hair - Eko Rado; Emelda Thesalonika; Radode Kristianto (MultiTech Publisher, 2023)
This research aims to determine the influence of video-based audio-visual media on the learning outcomes of class V students. Theme 2 Clean Air for Health, sub-theme 1, how the body processes clean air at SD Negeri 09785 Rambung Merah, the method in this research is a quantitative method, a type of experiment that takes the form of a research design. is a pre-experimental type one group pretest-posttest. Conducted in October 2023, the population in this research was all 24 students in class V of SDN 097805 Rambung Merah with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of video-based Audio Visual media. , audiovisual media are media/tools that are audible, meaning they can be heard, and tools that are visible, meaning they can be seen. In another sense, audiovisual media is a tool that can produce sound and appearance in one unit . The data collection technique is a test technique with tests of validity, reliability, level of difficulty and test of differentiability of questions. The test results used the Normality test, Homogeneity test, N-Gain test and Anova test with the help of the SPSS version 23 program. Based on the calculation results, the average value was obtained, the mean N-Gain score was 0.7339, meaning the data was in the medium category. The percentage of N-Gain is 73.3911% and from the results of significance in the anova test it is 0.000 which means the significant value is 0.000 < 0.005. This means that the data shows that there is an influence or Ha is accepted. This means that there is an influence of video-based audio-visual media on the learning outcomes of class V students in theme 2 clean air for health, sub-theme 1 how the body manages clean air at SD Negeri 097805 Rambung Merah.